Utilization of insecticide treated nets against malaria among pregnant women in Southern Nigeria - J. O., Odoko; E. U., Nwose; E. O., Igumbor (International Journal of Research in Medical Sciences, 2017)
Malaria remains one of the most important causes of maternal and child morbidity and mortality in sub-Saharan African, despite the availability of effective intervention. Pregnant women are susceptible to symptomatic malaria due to the invasion of the placenta by Plasmodium. There are public health endeavours in promoting use of insecticide treated nets (ITNS), but there is dearth of data on effectiveness of such endeavour. This narrative review looks briefly at the historical background of use of ITNS against malaria, Government policy and program evaluation process on free ITNS for vulnerable groups, relevance of knowledge in use of insecticide treated nets among pregnant mothers, and the role of attitude and practice on effective use of ITNS in prevention of malaria. There is evidence that relatively few people in high-risk regions access and use ITNS. The low utilization of ITNs attributable to perceived cost, inability to adjust to size of the beds, and side-effects heat and ventilation when slept under it.